EFFECT OF GROWTH CONDITIONS ON BIOFILM FORMATION BY PHENOL-DEGRADING BACTERIA ISOLATED FROM POLLUTED AND NON-POLLUTED SOURCES - Arifah Khusnuryani; Erni Martani; Tri Wibawa; Jaka Widada (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
Our previous research have isolated four phenol degrading bacteria. There are ATA6, DOK135, and DL120 which isolated from polluted source (hospital wastewater), also HP3 which isolated from non polluted source (peat soil). The purpose of this research is to analyze the effect of some environmental factors on the ability of four isolates to form biofilm. The environment factors were varied, such as growth medium, incubation temperature, and medium pH. Biofilm formation was measured using microtiter plate and crystal violet method, and the absorbance was read with microtiter auto reader at wavelenght 490 nm. The result showed that ATA6 was a strong biofilm former, DOK135 and HP3 were moderate biofilm former, and DL120 was a weak biofilm former. The results indicate that there is variation in the ability of selected isolates to form biofilm on various environmental factors. Generally, the isolates formed thicker biofilm in TSB medium which is a complex medium that provide more complete nutrient and formed biofilm optimally at 30oC. ATA6 formed biofilm optimally at pH 7 and HP3 at pH 9, while pH treatment did not affect on isolates DOK135 and DL120 to form biofilm.